Analisis Produksi, Keuntungan Dan Pola Pengeluaran Rumah Tangga Petani Belimbing Desa Waringinsari Kecamatan Langensari Kota Banjar - Ati Rosliyati; Candra Nuraini; Octaviana Helbawanti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The superior horticultural commodity, namely starfruit, has great potential in increasing farmers' income, especially in the Langensari area, Banjar City. However, the need to increase household expenditure efficiency is a challenge that must be overcome. Thus, it is important to analyze how the profits and expenditure patterns of starfruit farmers' households in Langensari The method used in this study is the survey method and the analysis method used is income analysis and R/C ratio. The results of the study of the average profit per hectare of starfruit farming in Langensari District, Banjar City is IDR 103,536,510.30. With an R/C value of 3.19, it shows that it has a very high efficiency value. The pattern of household expenditure of farmers with a total average expenditure of IDR 3,016,394, which is divided into Household Needs of 77%, Education Expenditure of 21.3%, Health Costs of 1.73%, and PBB expenditure of 0.17%.